2021
DOI: 10.2147/ijgm.s311021
|View full text |Cite
|
Sign up to set email alerts
|

Development and External Validation a Novel Inflammation-Based Score for Acute Kidney Injury and Prognosis in Intensive Care Unit Patients

Abstract: Purpose We aimed to evaluate the predictive ability of an integrated score based on several inflammatory indices of acute kidney injury (AKI) in patients in the intensive care unit (ICU). Patients and Methods In this observational study, 2555 patients from the Medical Information Mart for Intensive Care III database were randomly assigned to the test set (n=1599) and internal validation set (n=656). Moreover, 412 coronary care unit patients from Zhongnan Hospital, Wuhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In the present study, there was no association between the modified DNI, MLR, PLR and SII index and the occurrence of AKI. Although there are some previous studies that suggested that these ratios are associated with AKI, they were performed in other settings (e.g., postoperative or ICU) or with other types of ratio measurements (e.g., DNI requires measuring myeloperoxidase-reactive cells and a nuclear lobularity assay) [28,[31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was no association between the modified DNI, MLR, PLR and SII index and the occurrence of AKI. Although there are some previous studies that suggested that these ratios are associated with AKI, they were performed in other settings (e.g., postoperative or ICU) or with other types of ratio measurements (e.g., DNI requires measuring myeloperoxidase-reactive cells and a nuclear lobularity assay) [28,[31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…However, this tool was so complicated that it might be difficult for clinicians to use in clinical practice and the predictive accuracy was also relatively low (C-index = 0.66). 14 Moreover, several nomograms had been established in previous studies in patients with sepsis or in patients in ICU, 15 , 16 nevertheless, limited data are available for predicting pAKI for critical care unit patients until now. Hence, in the current study, we tested novel common variables to develop and validate a useful nomogram for predicting pAKI in two large critical care databases.…”
Section: Introductionmentioning
confidence: 99%